Metrics Model to Complement the Evaluation of DevOps in Software Companies - Orozco-Garcés, Carlos-Eduardo; Pardo-Calvache, César-Jesús; Suescún-Monsalve, Elizabeth (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This article presents a model to complement the evaluation of DevOps in software companies. It was designed by harmonizing the elements of the DevOps process identified through a systematic mapping of the literature and aimed to know the state of the art of methodological solutions and tools to evaluate DevOps in the industry. The process elements were identified, compared, and integrated into a common process structure that was used to establish a total of 11 metrics using the Goal-Question-Metric approach. The model was evaluated by a focus group of expert DevOps professionals. They determined that the model is clear, easy to apply, and provides valuable information to companies to improve their DevOps practices.